PLACE AND ROLE OF LEGAL CASE IN THE LEGAL SYSTEM OF UKRAINE - Pilgun, Natalia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose the article is devoted to the coverage of one of the current problems of law-making activity of officials and public authorities regarding the value and significance of legal precedent in Ukraine. Methods: general science: methods comparison, abstractions, system. Results: legal precedent is the main source of law in the Anglo-Saxon legal system, but it is also reflected in the Romano-Germanic legal family. Judicial practice of foreign countries clearly demonstrates the effectiveness and value of judicial precedent in resolving legal cases. Discussion: the peculiarity of the precedent is that the results of the interpretation of constitutional acts and ordinary laws provided by higher courts are binding on all lower levels of the judiciary. As a result of this approach, a relatively independent type of precedent is formed - the precedent of interpretation, recently the concept of precedent of interpretation is becoming increasingly relevant for Ukraine in connection with the practice of the Constitutional Court of Ukraine. According to the Constitution of Ukraine, the Constitutional Court of Ukraine has the exclusive right to provide an official interpretation of the Constitution and laws of Ukraine. Decisions of the Constitutional Court of Ukraine on official interpretation are binding on all individuals and legal entities, as well as public authorities and local governments in Ukraine. However, the Constitutional Court of Ukraine carries out interpretive activities not only within the framework of a special procedure, but also during decisions on compliance with the Constitution of Ukraine, laws and other legal acts specified by law. The motivating part of these decisions may contain legal interpretative provisions, which disclose the content of the relevant provisions of the Constitution of Ukraine and legal acts, the constitutionality of which has been verified. Judicial precedent has certain advantages in terms of the quality of justice, as it is characterized by special regulation of similar specific life situations, which reduces the level of arbitrariness of officials. However, there is another view of this issue, which denies the effectiveness and reliability of this mechanism, because the court precedent actually denies the individualization of the legal case.